(untitled) (Journal of Biomedical Investigation, 2025)
Background: Glycated haemoglobin (HbA1c) has been suggested to be a better predictor for coronary heart disease and strongly associated with atherosclerosis. Changes in lipid profile is linked with severity of diabetes as adjudged by HbA1c. Lipid abnormalities are common in type 2 diabetics, but the pattern may vary between ethnic groups. Aim: The current study was undertaken to explore the association of HbA1c and serum lipid profile parameters in type 2 diabetics among persons of three ethnic groups in Sokoto. Methods: The current study was a cross-sectional case-control study. The Cochran formula was used to determine the number of subjects recruited. Demographic and clinical characteristics were obtained from all the participants. HbA1c and lipid profile parameters were determined using standard laboratory tests. Ranges for TC <200mg/dl, TG <150mg/dl, LDL-c <100mg/dl and ranges between 51-60 for females and 41-60 for males for HDL-c were considered dyslipidaemia. All data were presented using mean and standard deviation, while independent samples t-test and one-way analysis of variance (ANOVA) followed by Bonferroni multiple comparison test to evaluate the mean differences between the groups at statistical significance of <0.05. Results: The mean values for serum HbA1c were slightly higher in diabetic groups (7.58±0.87 for Hausa/Fulani, 7.23±0.58 for Igbo and 7.34±0.67 for Yoruba) compared to their corresponding control groups (5.21±0.56 for Hausa/Fulani, 5.15±0.55 for Igbo and 5.21±0.55 for Yoruba) with p <0.0001. Serum levels of total cholesterol, triglyceride and LDL-c in diabetic group (207.99±89.82, 183.16±60.76 and 101.27±52.19 respectively) were higher than the control group (161.68±27.64, 137.14±24.18 and 90.16±28.14 respectively) p <0.0001; whereas, HDL-c was decreased in diabetics (37.26±12.90) than the control group (46.64±11.15) p <0.005. The HbA1c correlated with increased TC, TG and LDL-c (r = 0.483269, 0.623952 and 0.390193 respectively) p=0.0001 and decreased HDL-c level (r= -0.247900) p=0.0001. Conclusion: It was concluded that HbA1c is positively correlated to dyslipidaemia. HbA1c may be considered as an indirect predictor for dyslipidaemia. The current study therefore, recommend adequate glycaemic control via serum evaluation of HbA1c among type 2 diabetics irrespective of ethnic background.